Genes possibly related to symbiosis in early life stages of Acropora tenuis inoculated with Symbiodinium microadriaticum - Yoshioka, Yuki; Chiu, Yi-Ling; Uchida, Taiga; Yamashita, Hiroshi; Suzuki, Go; Shinzato, Chuya (Communications biology, 2023)
Due to the ecological importance of mutualism between reef-building corals and symbiotic algae (Family Symbiodiniaceae), various transcriptomic studies on coral-algal symbiosis have been performed; however, molecular mechanisms, especially genes essential to initiate and maintain these symbioses remain unknown. We investigated transcriptomic responses of Acropora tenuis to inoculation with the native algal symbiont, Symbiodinium microadriaticum , during early life stages, and identified possible symbiosis-related genes. Genes involved in immune regulation, protection against oxidative stress, and metabolic interactions between partners are particularly important for symbiosis during Acropora early life stages. In addition, molecular phylogenetic analysis revealed that some possible symbiosis-related genes originated by gene duplication in the Acropora lineage, suggesting that gene duplication may have been the driving force to establish stable mutualism in Acropora , and that symbiotic molecular mechanisms may vary among coral lineages. Investigation of the transcriptomic responses of Acropora tenuis to inoculation with the native algal symbiont identifies genes that may support coral-algal symbiosis during early life stages of corals.